POLYMORPHISMS OF THE PROGESTERONE RECEPTOR GENE IN ENDOMETRIOSIS PATIENTS OF SOUTH SUMATRA, INDONESIA - Muhammad Irsan Saleh; Rizki Andini Nawawi; Subandrate Subandrate (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Polymorphisms of the progesterone receptor gene alter the expressions of two receptor isoforms involved in the regulation of progesterone's antiproliferative effect in endometriotic tissue. This study aims to identify the +331G/A polymorphism of the progesterone receptor gene in endometriosis patients in Palembang, South Sumatra. Identification of +331G/A single-nucleotide polymorphism (SNP) was conducted on 42 endometriosis patients through polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). In this study, twenty-six (61.9%) subjects had heterozygous mutant genotype for the +331G/A SNP. No subject with homozygous mutant genotype for the +331G/A polymorphism was identified. The frequencies of polymorphic alleles for the +331G/A polymorphism was 30.9%. In conclusion, the +331G/A progesterone receptor gene polymorphism was present in endometriosis patients in Palembang, South Sumatra. This finding may warrant further studies to determine whether this polymorphism play a role in the development of endometriosis in the Indonesian population.